An inconvenient truth : [videorecording (DVD)] : a global warning - Guggenheim, Davis; Gore, Al, 1948- (Paramount Pictures, 2006)
A passionate and inspiring look at former Vice President Al Gore's campaign to expose the myths and misconceptions of global warming, and to create public awareness on the subject.